Plan of Northumberland Sound, Prince Albert Island by Captn. Sir Edwd. Belcher, Posn. of Winter Quarters . 1852-3 / published according to Act of Parliament at the Hydrographic Office of the Admiralty August 8th 1855 - Belcher, Edward, Sir, 1799-1877 (Hydrographic Office of the Admiralty, 1855)
[Chart no.] 2381. Color;